Interaksi Antara Iklim, Tanah Dan Tanaman Tahunan - Karyati, Karyati (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2014)
Interaction among climate, soil, and plants are very important dan influenced on each other. This paper was to inform suitability of climate and soil factors for perennial plants. The perennial plants were classified into plantation and forestry plants. Requirement of climate and soil factors for perennial plants was documented descriptively. Generally, many perennial plants need range annual 500-3,000 mm/year of rainfall, 15-34oC of monthly temperature, 70-90% of monthly relative humidity, and pH of 4.0-8.5. Information on suitability among species of perennial plants, climate elements, and soil properties for perennial plants is needed to support the success of plantation and forest programs. The plantation and forest programs are planned in large scale and long term, therefore selection of the appropriate plant species is vital for determine the successful of planting program.Key words: Climate element, soil properties, perennial plant, plantation plant, forest plant.